Value and Culture Based Marketing: The Key to Employee and Consumer Engagement in Indonesia - Reina A. Hadikusumo (Side: Scientific Development Journal, 2025)
This article explores the pivotal role of value and culture-based marketing in enhancing employee and consumer engagement within the Indonesian context. Employing a qualitative literature review, the study synthesizes recent research and case studies to examine how marketing strategies rooted in local values and cultural nuances can foster deeper connections with both internal and external stakeholders. The findings indicate that Indonesian companies leveraging value-driven and culturally resonant marketing approaches are more successful in building trust, loyalty, and advocacy among employees and consumers. Value-based marketing, which emphasizes functional, emotional, and experiential benefits, is shown to increase satisfaction and voluntary brand advocacy, particularly when integrated with digital platforms such as social media. Furthermore, culture-based marketing strategies that align with Indonesia’s diverse traditions and social norms enhance the authenticity and relevance of brand messages, leading to stronger engagement and sustained relationships. The literature also highlights the importance of co-creation and participatory approaches, where employees and consumers are actively involved in shaping brand experiences, thus reinforcing organizational identity and competitive advantage. Despite these advantages, challenges such as balancing global brand consistency with local adaptation remain. This study contributes to the growing body of knowledge on marketing in emerging markets by providing insights into the mechanisms through which value and culture-based strategies drive engagement. The results offer practical implications for marketers and managers seeking to optimize engagement and performance in Indonesia’s dynamic business landscape.